Human trafficking in the Sinai : refugees between life and death - Reisen, Mirjam van (Wolf Legal Publishers, 2012)
This report describes the horrific situation of trafficking of refugees in the Sinai desert, a crisis that started in 2009. The refugees include men, women, children and accompanying infants fleeing from already desperate circumstances in Eritrea, Ethiopia and Sudan. An estimated 95% of the refugees held as hostages in the Sinai (also referred to as hostages) are Eritreans. Smuggled across borders by middlemen, or kidnapped from refugee camps in Ethiopia and the Sudan as well as their surrounding areas, and then captured or sold, the refugees are held hostage close to the Israeli border in inhumane conditions and tortured for ransoms up to USD 50,000. A large number of the refugees have died, either while being held hostage or after their release - often even after their ransom has been paid. A large number of refugees simply `disappear`, killed while being held or shot.